Development of a Hypothetical Learning Trajectory for Systems of Linear Equations in Three Variables Based on PMRI Using the Context of Hijab Accessories: A Pilot Experiment Study - Intan Buhati Asfyra; Syamsinar (International Journal of Technology and Education Research, 2026)
Systems of Linear Equations in Three Variables (SLETV) based on Indonesian Realistic Mathematics Education (PMRI) using the context of hijab accessories supported by Information and Communication Technology (ICT). The research employs a design research method of the validation study type, consisting of three phases: preparing for the experiment, design experiment, and retrospective analysis, with a focus on a pilot experiment involving six tenth-grade students majoring in Fashion Design at SMK Negeri 6 Palembang. Data were collected through observation, interviews, and documentation, and analyzed retrospectively. The results show that the developed HLT facilitates students’ understanding of SLETV concepts gradually through a process of mathematization from real-world contexts to formal mathematical forms, although some procedural errors in algebraic operations were still found. In addition, the use of the hijab accessories context and ICT support increased students’ engagement in the learning process. Based on the retrospective analysis, revisions to the HLT were made in terms of scaffolding, strengthening algebraic operations, and providing more varied contextual problems, resulting in a more optimal and meaningful learning design.